Vernacularization Of Javanese Hadith Translations: Al-qaul Al-mugīṡ Ála lubāb Al-ḥadīṡ By KH. Misbah Mustafa - Sakinah, Fatihatus (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
This study investigates the forms of vernacularization in KH Misbah Mustafa's hadith translation of al-Al-Qaul al-Mugīṡ ála Lubāb al-Ḥadīṡ. Kitab al-Al-Qaul al-Mugīṡ ála Lubāb al-Ḥadīṡ is a translation of traditions from the book Lubāb al-Hadis by Jalāl al-Dīn al-Suyuthi. The translated text is presented by Misbah Mustafa using Javanese pegon language. The research conducted is library research with primary data from Kitab al-Al-Qaul al-Mugīṡ ála Lubāb al-Ḥadīṡ. The analysis used is narrative analysis using Anthony H. Johns' vernacularization. The results of this study show that the translation of an Arabic work into a local language will definitely bring elements of locality that are accommodated in the translation process. The existence of this makes it easier for people to read and accept the teaching values in the hadith. This process is an important element closely related to the translator's accommodating attitude towards Javanese cultural values. The forms of vernacularization found are vernacularization in appearance, using pegon script and gandul meaning, the use of Javanese language and local diction such as semut pudak, ketigo, and gaman.